2018
DOI: 10.1002/jmv.25198
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Zika virus and Rubella virus IgG among blood donors in Rwanda and in Sweden

Abstract: Seroprevalence studies provide information on the susceptibility to infection of certain populations, including women of childbearing age. Such data from Central Africa are scarce regarding two viruses that cause congenital infections: Zika virus (ZIKV), an emerging mosquito-borne infection, and Rubella virus (RuV), a vaccine-preventable infection. We report on the seroprevalence of both ZIKV and RuV from Rwanda, a country without any known cases of ZIKV, but bordering Uganda where this virus was isolated in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…In Bolivia the ZIKV seroprevalence among blood donors was 39.0% in Beni and 25.1% in Santa Cruz departments, 20 in Suriname it was 35.1% 21 (urban and rural population), in Nicaragua: 36.1%, 45.8% and 56.4% in pediatric, household and adult cohorts 22 respectively, while in Northeast Brazil (63.3%) (total ZIKV seroprevalence for HIV-infected, tuberculosis patients and pregnant women). 23 On the other hand, in other regions of the world the ZIKV seroprevalence among blood donors was lower or similar to our results, examples being Rwanda (1.4%) 24 , Cameroon (5%) 25 and Laos (4.5 −9.9%). 26 The difference in ZIKV seroprevalence can be explained on one Our study demonstrated a significant difference between the obtained ZIKV seroprevalence by ELISA and PRNT tests.…”
Section: Discussionsupporting
confidence: 89%
“…In Bolivia the ZIKV seroprevalence among blood donors was 39.0% in Beni and 25.1% in Santa Cruz departments, 20 in Suriname it was 35.1% 21 (urban and rural population), in Nicaragua: 36.1%, 45.8% and 56.4% in pediatric, household and adult cohorts 22 respectively, while in Northeast Brazil (63.3%) (total ZIKV seroprevalence for HIV-infected, tuberculosis patients and pregnant women). 23 On the other hand, in other regions of the world the ZIKV seroprevalence among blood donors was lower or similar to our results, examples being Rwanda (1.4%) 24 , Cameroon (5%) 25 and Laos (4.5 −9.9%). 26 The difference in ZIKV seroprevalence can be explained on one Our study demonstrated a significant difference between the obtained ZIKV seroprevalence by ELISA and PRNT tests.…”
Section: Discussionsupporting
confidence: 89%
“…Recently, a number of serosurveys of ZIKV infections have been conducted in Oceania, Africa, Latin America, and the Caribbean. The seroprevalence was high in Micronesia (73%) [23], Brazil (63.3%) [24], Nicaragua (36 – 56%) [25], French Polynesia (49%) [26], Martinique (42.2%) [27], Bolivia (0 – 39%) [28], Suriname (35.1%) [29], French Guiana (18.8%) [30], Saudi Arabia (12.68%) [31], and Nigeria (10%) [32], but was less than 10% in Laos (9.9%) [33], Indonesia (9.1%) [17], Zambia (6.1%) [34], Cameroon (5%) [35], Rwanda (1.4%) [36], and Kenya (0.24 – 7.11%) [37]. However, the laboratory assays used were varied across the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Seroprevalence studies were conducted in 49 countries and territories, with a total of 63,864 individuals involved. These studies comprised 18 countries in Africa (including Burkina Faso [ 8 ], Cape Verde [ 9 ], Cameroon [ 10 ], Democratic Republic of the Congo [ 11 ], Ethiopia [ 12 ], Gabon [ 13 ], Ghana [ 14 ], Kenya [ 15 , 16 ], Madagascar [ 17 ], Mali [ 18 , 19 ], Nigeria [ 20 24 ], Republic of the Congo [ 25 ], Rwanda [ 26 ], Senegal [ 18 ], Sudan [ 27 ], Tanzania [ 28 ], The Gambia [ 18 ], and Zambia [ 29 , 30 ]); 13 countries in the Americas (Bolivia [ 1 ], Brazil, Colombia, French Guiana (see references in S2 Table ), Guatemala [ 31 ], Honduras [ 32 ], Jamaica [ 33 ], Martinique [ 34 ], Mexico [ 32 , 35 ], Nicaragua (references in S2 Table ), Peru [ 36 ], Puerto Rico [ 32 ], and Suriname [ 37 ]); 3 countries in the Eastern Mediterranean (Iran [ 38 ], Iraq [ 39 ], Saudi Arabia [ 40 ]); 3 countries in Europe (Cyprus [ 41 ], France [ 42 ] and Sweden [ 26 ]); 2 countries in Southeast Asia (Indonesia, Thailand (references in S2 Table ); and 10 countries in the Western Pacific region (China [ 43 45 ], Fiji […”
Section: Resultsmentioning
confidence: 99%